Quarterback rush - Bowen, Carl.; Garcia, Eduardo, 1970 August 31- (North Mankato, Minn. : Stone Arch Books, a Capstone imprint, 2015)
The Otters keep leaving their game on the practice field and losing their football games--so wide receiver Steve Michaels must overcome his own frustrations and help Aaron Corbin, his quarterback, get past his fears and play like the champion he can be.
3.3
3-6
3-6
3.3.
3-6
Keywords: Quarterbacks (Football) -- Comic books, strips, etc. -- Juvenile fiction; Wide receivers (Football) -- Comic books, strips, etc. -- Juvenile fiction; Football -- Comic books, strips, etc. -- Juvenile fiction; Teamwork (Sports) -- Comic books, strips, etc. -- Juvenile fiction; Self-confidence -- Comic books, strips, etc. -- Juvenile fiction; Quarterbacks (Football) -- Fiction; Wide receivers (Football) -- Fiction; Football -- Fiction; Teamwork (Sports) -- Fiction; Self-confidence -- Fiction; Sports -- Fiction; Cartoons and comics; Quarterbacks (Football) -- Comic books, strips, etc. -- Fiction; Wide receivers (Football) -- Comic books, strips, etc. -- Fiction; Football -- Comic books, strips, etc. -- Fiction; Teamwork (Sports) -- Comic books, strips, etc. -- Fiction; Self-confidence -- Comic books, strips, etc. -- Fiction; Sports -- Comic books, strips, etc. -- Fiction; Comic books, strips, etc; Graphic novels